Associations Between Delivery Modes, Birth Outcomes and Offspring Anxiety Disorders in a Population-Based Birth Cohort of Children and Adolescents - Ståhlberg, Tiia; Upadhyaya, Subina; Polo-Kantola, Päivi; Khanal, Prakash; Luntamo, Terhi; Hinkka-Yli-Salomäki, Susanna; Sourander, Andre (Frontiers in Psychiatry, 2022)
Mode of delivery and well-being markers for newborn infants have been associated with later psychiatric problems in children and adolescents. However, only few studies have examined the association between birth outcomes and anxiety disorders and the results have been contradictory. This study was a Finnish population-based register study, which comprised 22,181 children and adolescents with anxiety disorders and 74,726 controls. Three national registers were used to collect the data on exposures, confounders and outcomes. Mode of delivery, the one-minute Apgar score, umbilical artery pH and neonatal monitoring were studied as exposure variables for anxiety disorders and for specific anxiety disorders. Conditional logistic regression was used to examine these associations. Unplanned and planned cesarean sections increased the odds for anxiety disorders in children and adolescents (adjusted OR 1.08, 95% CI 1.02-1.15 and aOR 1.12, 95% CI 1.05-1.19, respectively). After an additional adjustment for maternal diagnoses, unplanned cesarean sections remained statistically significant (aOR 1.11, 95% CI 1.04-1.18). For specific anxiety disorders, planned cesarean sections and the need for neonatal monitoring increased the odds for specific phobia (aOR 1.21, 95% CI 1.01-1.44 and aOR 1.28, 95% CI 1.07-1.52, respectively). Birth by cesarean section increased the odds for later anxiety disorders in children and adolescents and unplanned cesarean sections showed an independent association. Further studies are needed to examine the mechanisms behind these associations.